Analysis of Employee Loyalty, Work Discipline and Employee Skills on Performance Improvement through SOP - Arifin, Mochamad Djainul Djainul; Supardi, Supardi (Universitas Islam Kadiri, 2024)
This research aims to examine the correlation between employee loyalty, workplace politeness, and employee competence and performance improvement in the district, with Standard Operating Procedures (SOP) as the intervention variable. Quantitative methodology is employed to gather data from district personnel through surveys and statistical analysis. The theoretical constructs of employee loyalty, workplace politeness, employee competence, and SOP as a management tool are applied in this research. The anticipated outcomes of this study are to provide a deeper understanding of the factors influencing employee performance in the district and to offer recommendations for enhancing human resource management in local government agencies. The theoretical and practical implications of these findings are discussed within the framework of strengthening management efficiency at the local level. This study establishes a foundation for formulating more effective management strategies to enhance employee performance in the district and may serve as a reference for future research in the human resource management domain within the government sector. Employee loyalty influences SOP. Work discipline influences SOP. Employee skills influence SOP. Employee loyalty influences performance improvement. Work discipline influences performance improvement. Employee skills influence performance improvement. SOPs have an effect on improving performance. Employee loyalty influences performance improvement through SOPs. Work discipline influences performance improvement through SOPs. Employee skills influence performance improvement through SOPs.